2004
DOI: 10.1002/jat.994
|View full text |Cite
|
Sign up to set email alerts
|

Gas chromatographic determination of cocaine and its metabolites in blood and urine from cocaine users in northwestern Spain

Abstract: A gas chromatographic method with fl ame ionization detection (GC/FID) was developed for the determination of cocaine and its metabolites in blood and urine samples from cocaine users in Northwestern Spain. After a solid-phase extraction with Bond Elut Certify cartridges and a derivatization with bis-trimethylsilyltrifluoroacetamide-trimethylchlorosilane (1%), calibration curves were constructed over 0.4-4 micro g ml(-1) for urine and 0.1-2 micro g ml(-1) for blood, using proadifen as the reference compound. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 19 publications
1
6
0
3
Order By: Relevance
“…The ratios obtained from the average urine concentrations showed that morphine was higher than MAM and codeine, BEG higher than cocaine and cocaethylene, and EDDP higher than methadone. Cocaine and BEG urine levels in our series were similar to those obtained by Peterson et al (1995) but higher than those published by Fernández et al (2004).…”
Section: −1supporting
confidence: 72%
“…The ratios obtained from the average urine concentrations showed that morphine was higher than MAM and codeine, BEG higher than cocaine and cocaethylene, and EDDP higher than methadone. Cocaine and BEG urine levels in our series were similar to those obtained by Peterson et al (1995) but higher than those published by Fernández et al (2004).…”
Section: −1supporting
confidence: 72%
“…Different structural properties of cocaine and its metabolite not only render immunological detection difficult For GC-MS, polar metabolites often need derivatisation for exact quantitation. Silylation by BSTFA-TMCS like for atropine and scopolamine was applied to cocaine and the metabolites benzoylecgonine and ecgonine methyl ester [53]. Several silylation steps [46] or derivatisation with several reagents according to the chemical nature of the metabolites [54] were successful for detection of methyl ecgonidine and thirteen further cocaine metabolites in human blood and urine, however, they demanded tedious sample preparation.…”
Section: Cocaine In Forensic Analysismentioning
confidence: 99%
“…A BSTFA/TMCS mixture was also shown to be effective for derivatization of the opioid analgesic buprenorphine in association with benzodiazepines, (40) as well as cocaine and derivatives (41,42) before GC/MS. Seven diverse pharmaceuticals including caffeine, estradiol, ibuprofen, ketoprofen, musk ketone, naproxen, and triclosan were also more effectively derivatized using the BSTFA + TMCS combination as compared to TMSI.…”
Section: Silylationmentioning
confidence: 99%